2018
DOI: 10.1177/1077699018785890
|View full text |Cite
|
Sign up to set email alerts
|

Moving Closer to the Action: How Viewers’ Experiences of Eyewitness Videos in TV News Influence the Trustworthiness of the Reports

Abstract: This study develops and tests a theoretical model of viewers’ experiences of eyewitness videos (EWVs) in TV news reports and the resulting effects on perceived trustworthiness. It builds on qualitative research suggesting that the visual characteristics of EWVs cause specific effects, namely feelings of presence and empathy as well as perceptions of authenticity and bias. By conducting an online experiment ( N = 328), it was tested whether embedding an EWV in a report about the Ukraine conflict influences perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…By increasing transparency and including eyewitness videos, information providers earn more trust among the viewing audience. In a previous study examining the conflict in Ukraine in the TV news, analysts found that eyewitness videos affect perceptions of trustworthiness through "feelings of presence and empathy as well as perceptions of authenticity and bias" [Halfmann et al, 2019].…”
Section: Discussionmentioning
confidence: 99%
“…By increasing transparency and including eyewitness videos, information providers earn more trust among the viewing audience. In a previous study examining the conflict in Ukraine in the TV news, analysts found that eyewitness videos affect perceptions of trustworthiness through "feelings of presence and empathy as well as perceptions of authenticity and bias" [Halfmann et al, 2019].…”
Section: Discussionmentioning
confidence: 99%
“…By 2020, the focus of trustworthiness research is mainly on experiences, mechanisms, individual differences, testimony, and quality. For example, how the audience's experience of sighting video in TV news affects the trustworthiness of reports (e.g., Halfmann et al, 2019); trust behavior and brain neurons (e.g., Wang et al, 2018;Zebrowitz et al, 2018). As of 2023, the current research focus has changed to health, determinants, race, time, culture, automation, acceptance, distrust, and scale.…”
Section: Research Frontier Analysismentioning
confidence: 99%
“…It does so by providing alternative voices to a story, bringing new stories to journalists' attention, and by enabling journalists to report on developing stories without being in the vicinity themselves (Hellmueller & Li, 2015;Kleemans, Schaap, & Hermans, 2015;McNair, 2013). Also, perceptions of authenticity and presence increase due to the integration of eyewitness videos (Halfmann et al, 2018). On the other hand, UGC can have a detrimental effect on the audience's perception of correctness and verifiability of information as well as of the reliability of sources.…”
Section: Ugc and Journalism's Trustworthinessmentioning
confidence: 99%
“…Scholars and practitioners alike question the adequacy of social media as a source for journalism (Lewis & Molyneux, 2018), journalists struggle with the authenticity and impact of UGC (Murrell, 2018) and recipients are skeptical about including the audience in the process (Karlsson, Clerwall, & Nord, 2018). This might be the reason why UGC does not seem to directly increase journalistic trustworthiness (Grosser, Hase, & Wintterlin, 2019;Halfmann, Dech, Riemann, Schlenker, & Wessler, 2018).…”
Section: Introductionmentioning
confidence: 99%